La Teología Mística de Pseudo Dionisio Areopagita: una nueva lectura - Marcelo D. Boeri; José Pablo Martín (Tópicos, 2013)
In this paper a new Spanish translation of the brief opuscule De mystica theologia (by the Christian Neoplatonic Pseudo Dyonisius Areopagita) along with an introduction to the text are presented. The introduction focuses on the analysis of some points that are especially helpful to understand the text at issue: (i) its history and its significance for the Neoplatonism and, more importantly, its relevance in terms of a highly original exposition of the Christian doctrine from a Neoplatonist viewpoint, (ii) The importance of this text in Contemporary philosophy (Hegel, Heidegger, Wittgenstein) is also noted and, finally, (iii) its crucial significance for the so-called "negative theology".